Understanding medicine access strategies for innovator medicines registered in South Africa - Thulasizwe Njabulo Qiniso Jama; Fatima Suleman (BMC, 2024)
Abstract Background South Africa is composed of a two-tier healthcare system. One tier is a private healthcare system that is funded through medical insurance, and comprised of people who can afford to make monthly payments towards their medical insurance. Second tier is a government-funded public healthcare system, which covers the majority of the population. This study explored the perceived barriers and current strategies being utilised by the pharmaceutical industry to increase access to innovator medicines. Objectives The objectives of the study were to: (1) quantify and classify innovator medicines registered between 2010 and 2020 by the South African Health Products Regulatory Authority (SAHPRA); (2) identify barriers to accessing innovator medicines in South Africa through interviews with market access managers from innovator companies; and (3) explore the current market access strategies used by the pharmaceutical industry. Design This study employed a quantitative and qualitative methodology. Whereby the former involved the extraction of a list of innovator medicines from the regulator database, and the latter involved 9 semi structured interviews. Purposive sampling was conducted through pharmaceutical association member companies. The interviews included seven market access managers and two medicine managers from one of the payers in South Africa. Thematic analysis was used to interpret the data collected from the study. Results According to the regulator database during the review period, 238 innovator medicines were registered. Only 14.77% were available in the public sector in the form of tenders, whereas in the private sector (based on the products having a SEP), 76.92% were available. From the interviews six themes emerged: reimbursement of medicines, types of reimbursement, partnerships, technology, legislative challenges, and other factors (e.g., real-world evidence). Conclusion Access to innovator medicines in South Africa is a challenge, as the price of these therapies is high. Therefore, various stakeholders in the health sector must collaborate to identify and implement solutions that are locally relevant. The government needs to proactively update policies that would allow for alternative reimbursement methods to be explored.